Pinostrobin inhibits renal CFTR-mediated Cl− secretion and retards cyst growth in cell-derived cyst and polycystic kidney disease rats - Kanlayanee Tonum; Napason Chabang; Somsak Fongsupa; Suphat Chantawarin; Chutima Jiarpinitnun; Patoomrattana Tuchinda; Sunhapas Soodvilai (Elsevier, 2022)
Cystic fibrosis transmembrane conductance regulator (CFTR) plays crucial role in renal cyst expansion via increase in fluid accumulation. Inhibition of CFTR has been proposed to retard cyst development and enlargement in polycystic kidney disease (PKD). Pinostrobin, a bioactive natural flavonoid, possesses several pharmacological effects. The present study investigated pharmacological effects of pinostrobin on CFTR-mediated Cl− secretion and renal cyst expansion in in vitro and in vivo models. Pinostrobin (10 and 50 μM) reduced number of MDCK cell-derived cyst colonies and inhibited cyst expansion via inhibition of cell proliferation and CFTR-mediated Cl− secretion. The inhibitory effect of pinostrobin was not due to the decrease in cell viability and activity of Na+-K+-ATPase. We also investigated the natural analogue pinocembrin as well as the synthetic analogue pinostrobin oxime. Both pinocembrin and pinostrobin oxime did not reduce CFTR-mediated Cl− secretion. In PKD rats, oral administration of pinostrobin (40 mg/kg/day) exhibited a decreasing in cystic area compared to vehicle-treated rats. Pinostrobin treatment inhibited renal expression of CFTR protein in PKD rats. Our findings highlighted the potential therapeutic application of pinostrobin in PKD.